Zarys historii ruchu związkowego w Nigerii (1966-1999) - Kalejaiye, Kayode (Acta Universitatis Lodziensis. Folia Historica, 2005)
I have duelly analysed the role and impart of consequetive Nigerian governments on various aspects of trade-unionism and industrial relations in Nigeria from the year 1966 to the year 1998. I have therefore critically assessed the impact which these various governments have had on the Nigerian trade union movement during the 32 years of its existence. My analysis shows a definite and uncompromising policy of intervention and deep involvement in the affairs of Nigerian unions by mostly the various military governments which dominated Nigeria during the period analysed contary to what was the practice during the erstwhile civilian administration. For example on the negative side the ban on strikes from the year 1966-1979, but on the positive side however, several instances can be repeated from this publication where the military governments legislations and administrations were positively oriented toward the improvement of the trade unions, for example Decree (No. 36) of 1973, which gave effect to the Industrial Arbitration Tribunals award other examples are the trade union Decree of 1973 which compelled employers to accord recognition to any duly registered union and made illegal the use of funds in partisan parties also the trade disputes decree of 1976, which setup the National Industrial Court as the last institution in the apparatus for the settlement of trade disputes. But as noted the military never gave democracy any chance in Nigeria as noted they dominated in all affairs of the government by force to the day they finally left the Nigerian political stage in the year 1998. I duelly hope the present civilian government of Nigeria will make it it’s objective to correct all the wrongdoings of the military and lay a solid foundation for the Nigerian trade union movement.